Multidimensional Science Education on Performance Assessment Comprehensively with Collaborative Project Learning Based Model: Philosophy Perspective - Sudirman Sudirman; Muhammad Sarjan; Joni Rokhmat; Hamidi Hamidi; Iswari Fauzi (Pascasarjana, Mataram University, 2022)
Competency-based learning requires an assessment instrument capable of comprehensively measuring learning objectives in the cognitive, psychomotor and affective domains. Therefore, an alternative assessment model based on performance is needed. The purpose of writing this article was to find out whether it is possible to comprehensively assess performance based on collaborative project learning in multidimensional science education from a philosophical perspective through literature study. Performance appraisal is a continuous assessment process through the process of collecting various activity-based information as an object of assessment in various ways and tools. Based on the results and discussion of the literature review, performance assessment is a continuous assessment process using various strategies and methods (multi-methods) where in this article the author combined collaborative project-based learning methods. Project based learning provides opportunities for students to explore content and learning experiences using various ways that are meaningful to themselves and to conduct experiments collaboratively by combining various interrelated subjects. Exploration of authentic and complex problems based on tasks that have been designed to produce joint work for reporting project results. Collaborative project learning between subjects is essentially a learning system that allows students to actively seek, explore, and discover concepts and principles authentically by involving various groups as assessors through self-assessment and Peer Assessment. The comprehensive performance appraisal process is a multidimensional process and information is obtained from the assessment process on aspects of cognitive skills, attitudes, critical thinking, process skills and products as an integral part of the learning process by empowering students and educators.